The Development Strategy of Religious Tourism Area At Baiturrahman Mosque, Kampung Cibogo, Sukabumi Regency - Maulina Dian. P; Lely Mustika; Ima Rachima Nazir; Daniel Mambo (Greenation International Journal of Tourism and Management, 2023)
Indonesia has various tourism potentials ranging from natural tourism, religious tourism, culinary tourism, marine tourism and so on. Sukabumi Regency has religious tourism opportunities, namely the Baiturahman Mosque in the village of Cibogo. The Baiturahman Mosque has an interesting shape and architecture and has a visualized philosophy in its design. In addition, its position is also located on a hill in an area of 20 ha, equipped with a lake and vegetable plantations, but not yet developed. The purpose of this study was to map and select a strategy for developing religious tourism in the Baiturahman Cibogo Sukabumi Mosque area using the SOAR and QSPM methods. This research is expected to identify priority strategies to improve the quality and attractiveness of religious tourism areas as well as to have a positive impact on the environment and society. The research method uses SOAR (Strength, Opportunity, Aspirations, Result) and QSPM (Quantitative Strategic Planning Matrix) analysis to determine strategic priorities in realizing the development of the Baiturrahman Mosque religious tourism area. The results of the QSPM analysis led to carrying out a branding strategy for the religious tourism area of the Baiturahman Mosque by utilizing information technology, especially digital marketing, in the form of social media, content, websites and so on. In addition to strengthening branding, it is carried out in the form of maximum service to achieve visitor satisfaction and increase promotional and branding value. For this reason, collaboration with various parties is also needed, which will add to this branding strategy, professional travel, and tour partnerships, as well as elements of the mass media and government elements that support the development of religious tourism at the Baiturahman Mosque, Cibogo-Sukabumi can be guaranteed with the highest score of 2.5128.